2022
DOI: 10.1371/journal.pone.0269237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in physical and sedentary behaviors on mental health and life satisfaction during the COVID-19 pandemic: Evidence from China

Abstract: Background While restriction measures are critical in containing the COVID-19 outbreak, limited studies have investigated the behavioral and psychological impact of these measures. This study aimed to investigate the effects of physical and sedentary behavioral changes and online behavior during the COVID-19 pandemic on mental health and life satisfaction among the Chinese population. Methods The data were obtained from a cross-sectional survey of 2145 residents aged between 18 and 80 in Hubei province, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…When evaluating diet-related health risk behaviors combined with sedentary behavior, a higher prevalence ratio was observed for mental disorder symptoms. Sedentary behavior has been studied as a risk factor for mental illness as screen-based sedentary behaviors, such as the use of computer, television (TV), and social media, are likely to induce addiction and poor sleep quality, which can maximize levels of mental distress ( 15 , 62 ). Furthermore, it is suggested that the greater the time spent in sedentary behavior, the less social interaction and, therefore, the greater the feeling of loneliness and sadness ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When evaluating diet-related health risk behaviors combined with sedentary behavior, a higher prevalence ratio was observed for mental disorder symptoms. Sedentary behavior has been studied as a risk factor for mental illness as screen-based sedentary behaviors, such as the use of computer, television (TV), and social media, are likely to induce addiction and poor sleep quality, which can maximize levels of mental distress ( 15 , 62 ). Furthermore, it is suggested that the greater the time spent in sedentary behavior, the less social interaction and, therefore, the greater the feeling of loneliness and sadness ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some important changes observed in the lifestyle of the population after the beginning of the COVID-19 pandemic refer to food consumption ( 14 ) and an increase in sedentary behavior ( 15 ). This happened because restrictive measures reduced the frequency of purchases of fresh foods such as fruits and vegetables ( 16 ) to the institution of work at home, and interrupted leisure-time physical activity outside the home ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of mobile phone technology has transformed the way individuals communicate, work, and entertain themselves. While the increased use of mobile phones has numerous benefits, such as increased connectivity, it also has potential negative effects on mental health and well-being [ 1 ]. According to the 50th China Internet Development Statistics Report released by China Internet Network Information Center (2022) (CNNIC), as of June 2022, the size of mobile phone users in China was 1.05 billion.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest global estimates, more than 80.0% of adolescents and 27.0% of adults fail to meet the recommended levels of PA set by the WHO (3,4). Moreover, the COVID-19 pandemic has led to an increase in sedentary behavior (5), exacerbating the already prevalent issue of insufficient PA (6).…”
Section: Introductionmentioning
confidence: 99%